A multidimensional view of gradient change in velar acquisition in three-year-olds receiving phonological treatment. (September 2014) - MacLeod, Andrea A. N.; Glaspey, Amy M.
Abstract The acquisition of phonemes does not occur in an "all or nothing" manner; instead, children gradually acquire dimensions of phonological knowledge. This gradual acquisition of phonemes is explored in the present study by comparing three types of measures taken from speech samples of three preschool-aged girls with a Speech Sound Disorder. The process of acquisition of velar stops was measured during 16 weeks of Cycles based speech treatment. Three types of measures were used to study the gradual acquisition of velar stops: acoustic analyses using voice onset time (VOT) for initial consonants and vowel duration for final consonants, speech adaptability using the Glaspey Dynamic Assessment of Phonology, and phonetic accuracy based on phonetic transcription. The children were assessed prior-to, after 8, and after 16 sessions of treatment based on a modified Cycles approach. At the onset of the study, the children had begun the process of acquiring velar stops. Differences on acoustic measures and speech adaptability measures were observed for velars that were not reflected in the phonetic transcription. The acoustic analyses and the speech adaptability measures were more sensitive and incremental in showing change over time when compared to phonetic transcription, with fewer ceiling and floor effects across the children. Although the individual profiles of gradient change were not simple, the acoustic and adaptability measures provided additional information regarding gradient change, and support our argument that a necessary approach is one that describes multiple dimensions of a child's phonological knowledge.